Field evaluation of fungicides for management of Lasiodiplodia leaf blight of coconut - Latha, P.; Sudhalakshmi, C.; Suresh, J.; Karthikeyan, M.; Sumitha, S.; Jerard, B. Augustine (Journal of Plantation Crops, 2024)
Various fungal and phytoplasma diseases are adversely impacting coconut yield. Among them, leaf blight, primarily attributed to Lasiodiplodia theobromae, has emerged as a significant contributor to yield losses ranging between 10 to 25 percent. This study aimed to assess the efficacy of novel fungicide formulations in mitigating leaf blight in coconut palms. An experimental plot, organized using a Randomized Block Design, was established, consisting of five distinct treatments, each replicated four times. The findings reveal that systemic fungicides, specifically propiconazole and tebuconazole, exhibited notable efficacy in curtailing leaf blight when applied at concentrations of 250 ppm and 1000 ppm, respectively. The effective fungicide concentrations are considerably lower than other fungicides tested in the field trials. The results revealed that sequential root feeding of propiconazole 25.9% EC @ 5% (100ml/palm) and tebuconazole 25.9% EC @ 5% (100ml/palm) at three months interval reduced the leaf blight incidence (5.66 % reduction) over control compared to root feeding of same fungicides continuously at quartely interval (3.02 %) with in six months on currently it boosted the nut yield to 135 nuts per palm per annum, compared to the 99 nuts per palm per annum recorded in the control palms.